The expression and prognostic value of hypoxia-inducible factor- 1α and p53 in non-small cell lung carcinoma - Wan, Yuming; Li, Feng; Shen, Yali; Chen, Huijiao; Zhai, Yachao; Huang, Jing; Wang, Jin; Xu, Feng (Translational Cancer Research, 2018)
Background: The study was aimed to explore the expression of hypoxia-inducible factor-1α (HIF-1α) and p53 protein, as well as their correlation with clinicopathological features and survival in non-small cell lung carcinoma (NSCLC) patients. Methods: The overexpression of HIF-1α and p53 alteration was detected by immunohistochemistry in 50 paraffin-embedded tumor samples from NSCLC patients who received pulmonary surgery and seven benign lung lesion tissue samples. In addition, the correlation between HIF-1α or p53 protein overexpression and clinicopathological features as well as their relationship with epidermal growth factor receptor (EGFR) overexpression was examined by the chi-squared test, while Kaplan-Meier survival analysis was applied to explore their prognostic value. Results: The results showed that HIF-1α and p53 protein overexpression in NSCLC was remarkably higher than that in benign lung lesion tissue, with a positive rate of 40% and 42%, respectively. HIF-1α overexpression had an unfavorable impact on radiotherapy (P=0.047) and patient survival (P=0.002). However, multivariate analysis showed that HIF-1α was not an independent prognostic factor. There was a significant correlation between the overexpression of HIF-1α and tumor size (P=0.005), nodal metastasis (P=0.014) and pathological stage (P=0.023), while p53 overexpression was only significantly associated with the differentiation level. No correlation was found between p53 overexpression and survival. Conclusions: Both HIF-1α and p53 protein levels played a crucial role in participating in oncogenesis, and HIF-1α might be a risk factor for survival and a biological marker relevant to radioresistance. However, p53 had no prognostic value for survival.